Studi Tentang Preferensi Konsumen, Sifat Fisiko Kimia dan Nilai Organoleptik Sei Daging Babi asal Kupang (Nusa Tenggara Timur) - Soffy Soetji Widarti; Hari Purnomo; Djalal Rosyidi (Universitas Sebelas Maret (UNS), 2012)
Pork sei is a meat product from Kupang (East Nusa Tenggara) that produced traditionally using curing and smoking methods. The purpose of this study was to observe consumer preference, physico-chemical and organoleptic properties of pork sei which is currently very popular in East Nusa Tenggara. The research was carried out by the method of observation and experiment using Completely Randomized Design with three replications. The observations were carried out on four restaurants and pork sei consumer in Kupang. Variables measured were moisture, protein, fat and carbohydrate contents, pH, and organoleptic test including color, texture, taste and tenderness. The results showed that there was no significant difference among pork sei originated from the four selected restaurants on fat content, carbohydrate content, pH, texture and tenderness. However, the protein content, taste and color were different significantly (P < 0.05). Based on the effectivity index analysis, it can be concluded that the best samples was originated from restaurant A.